38 Differences In Resting Tendon Metabolism In Rowers: A Microdialysis Study Of Metalloproteinase 2 And 9. (5th September 2014) - Fullerton, Julia; Chaudhry, Saira; Waugh, Charlie
Abstract : Introduction: The reason women sustain more soft tissue injuries than men is still unknown2, yet sex differences in ligament injuries, especially ACL injuries and associated biomechanical differences have been investigated extensively. Interestingly, a systematic review of ACL rupture patterns1 found female athletes were more likely to sustain ACL injuries during the pre-ovulatory phase of the menstrual cycle, suggesting that changes in hormone levels that occur during the menstrual cycle may influence the risk of ACL rupture. Although there is an increasing body of evidence relating the influence of circulating hormones to connective tissue metabolism3, there is little evidence of differences in tissue metabolism between men and women. Matrix metalloprotease (MMP) activity is essential in maintaining the homeostasis of extracellular matrix (ECM) turnover. The primary aim of this study was to examine resting levels of MMP-2 and -9, which are involved in the degradation of several ECM components, to assess whether sex difference exist. Additionally, we examined MMP activity in relation to height and weight, hypothesising that larger individuals may exhibit greater MMP activity based on greater mechanical loading experienced during daily and exercising activities. Methodology: This study sampled 11 rowers of a similar training level (6 men, age 21.0 ± 1.4 years, height 182.0 ± 2.6 cm, weight 79.1 ± 7.9 kg; 5 women, age 22.3 ± 1.2 years, height 169.2 ± 6.6 cm, weight 62.0 ± 5.0 kg). Participants were required not to exercise for 48 h prior to study commencement. Dialysate samples of the patellar tendon peritendinous space were collected every 30 min for 90 min using Ringers solution infused via a microdialysis technique. Samples were analysed using gelatin zymography (10% SDS-acrylamide gels, polymerized with 1mg/ml porcine skin gelatin; the level of protein digestion shown by the zymogram is directly proportional to the amount of MMP activity), followed by densitometric analysis using ImageJ. MMP activity was examined with respect to sex using a repeated measures ANOVA, and with height and weight using a Pearson product correlation coefficient. Statistical analysis was done using SPSS, significance was accepted at p < 0.05. Results: No differences in MMP activity were found between men and women, although there was a trend (p = 0.098). The correlation between MMP-2 and -9 and height (r = 0.894 and 0.324, respectively) and weight (r = 0.894 and 0.723, respectively) were not significant. Discussion: Although no significant difference was observed, there was a trend of increased MMP-9 in men. There are two possible theories to explain this finding: either MMP-9 is elevated in men, which might partially explain the increased incidence of patellar tendinopathy in men (based on elevated levels of MMP-9 in tendinopathic tendons4), or MMP-9 is downregulated in women, which might indicate sub-optimum collagen turnover. Increasing the sample size of this study may provide more conclusive results and improve our understanding of tendon metabolism in men and women. In addition, activity of tissue inhibitor metallomatrix proteinases (TIMPs) should be examined to give an overall picture of tendon metabolism, as well as establishing the influence of oestrogen on tendon metabolism by taking menstrual cycle into consideration. References: 1 Hewett, et al . Am J Sports Med. 1998;35:659–668 2 Magusson, et al . Int J Exp Pathol. 88:237–240 3 Miller, et al . J ApplPhysiol . 1985;102:541–546 4 Parkinson, et al . Arthritis Rheum . 2010;62:3028–3035